Effects of exogenous organic acids on cadmium accumulation and cell wall components of Cosmos bipinnatus under cadmium stress - Xiaofang Yu; Xiaoxuan Zeng; Chunyu Fan; Xiaoyu Ming; Yujia Liu; Hanyue Xue; Yuwei Huang; Xinyu Zhang; Wenyu Ji; Maolin Chen; Junrui Zhang; Lijuan Yang; et al. (Ecotoxicology and Environmental Safety, 2025)
This study evaluated how citric acid (CA) and malic acid (MA) affect cadmium (Cd) accumulation and translocation in Cosmos bipinnatus under Cd stress. At the same time, principal component analysis (PCA) was used to analyze the distribution of Cd at different CA and MA concentrations. We selected 1 mM CA and 2 mM MA for further experiments and examined their effects on Cd distribution, subcellular localization, chemical forms, cell wall composition, FTIR spectra, and PME activity. Further comparisons revealed that CA significantly promoted Cd translocation to aboveground parts, resulting in increased Cd accumulation in leaves, whereas MA enhanced Cd retention in roots by elevating PME activity, thereby effectively restricting Cd movement toward stems and leaves. Accordingly, MA demonstrated greater potential in limiting Cd transport to key aboveground tissues, underscoring its suitability as a remediation agent for Cd-contaminated plants. These findings suggest that MA's underlying mechanism may enhance phytoremediation strategies for Cd-contaminated environments, providing valuable insights into optimizing plant-based remediation approaches for heavy metal pollution.